A Theory of Collateral for the Lender of Last Resort. (5th February 2021) - Choi, Dong Beom; Santos, João A C; Yorulmazer, Tanju
Abstract: We consider a macroprudential approach to analyze the optimal lending policy for the central bank, focusing on spillover effects that policy exerts on money markets. Lending against high-quality collateral protects central banks against losses, but can adversely affect liquidity creation in markets since high-quality collateral gets locked up with the central bank rather than circulating in markets. Lending against low-quality collateral creates counterparty risk but can improve liquidity in markets. We illustrate the optimal policy incorporating these trade-offs. Contrary to what is generally accepted, lending against high-quality collateral can have negative effects, whereas it may be optimal to lend against low-quality collateral.